PEMBERDAYAAN IBU SEBAGAI UPAYA DETEKSI DINI KEKURANGAN GIZI BALITA DI PUSKESMAS II SUMBANG KABUPATEN BANYUMAS - Kusumawati, Erna; Rahardjo, Setiyowati; Dardjito, Endo (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2015)
A mother has a mayor role in child growth, especially for their nutritional status. The objective of this research was to identify the incidence of undernutrition by identifying factors that cause undernutrition such as child factor, family factor, maternal factor and environmental factor using quantitive approach, identifying how far the interaction of community with the publich health, identifying the effectiveness programs to prevent undernutrition The factors analyzed using multiple regression logistic. Interactive model1) used to analyzed the extent of publich health for the undernutrition preventing programs. The sample of this study were the children with undernourished from January-July 2012, there were 50 subject. As a control, researcher use 50 children with wellnourished status who lives near the subject with undernourished status. Analysis of quantitative data obtained from the results of the causes of malnutrition in gender, maternal employment, and environmental sanitation. The most dominant factor is maternal employment. Qualitative analysis concluded institutional issues include the provision of supplementary feeding has been unable to overcome the problem of malnutrition, a history of maternal nutrition and low birth weight, low maternal education and knowledge, lack of exclusive breastfeeding, complementary feeding premature delivery, low maternal participation in posyandu and low income families. Early detection of malnutrition can be done by empowering housewives with increased knowledge of breastfeeding / complementary feeding and nutrition during pregnancy, maintenance of environmental sanitation, as well as increased participation of mothers in the Posyandu.